DIGITAL ECONOMY AND UZBEKISTAN: PROBLEMS AND SOLUTIONS (ResearchJet Journal of Analysis and Inventions, 2021)
This article will discuss current state of digital economy and will provide some relevant proposals for further improvements in this sphere in Uzbekistan